Recurrent EML4-NTRK3 fusions in infantile fibrosarcoma and congenital mesoblastic nephroma suggest a revised testing strategy - Church, Alanna J; Calicchio, Monica L; Nardi, Valentina; Skalova, Alena; Pinto, Andre; Dillon, Deborah A; Gomez-Fernandez, Carmen R; Manoj, Namitha; Haimes, Josh D; Stahl, Joshua A; Dela Cruz, Filemon S; Tannenbaum-Dvir, Sarah; et al. (Modern pathology, 2018)
Infantile fibrosarcoma and congenital mesoblastic nephroma are tumors of infancy traditionally associated with the ETV6-NTRK3 gene fusion. However, a number of case reports have identified variant fusions in these tumors. In order to assess the frequency of variant NTRK3 fusions, and in particular whether the recently identified EML4-NTRK3 fusion is recurrent, 63 archival cases of infantile fibrosarcoma, congenital mesoblastic nephroma, mammary analog secretory carcinoma and secretory breast carcinoma (tumor types that are known to carry recurrent ETV6-NTRK3 fusions) were tested with NTRK3 break-apart FISH, EML4-NTRK3 dual fusion FISH, and targeted RNA sequencing. The EML4-NTRK3 fusion was identified in two cases of infantile fibrosarcoma (one of which was previously described), and in one case of congenital mesoblastic nephroma, demonstrating that the EML4-NTRK3 fusion is a recurrent genetic event in these related tumors. The growing spectrum of gene fusions associated with infantile fibrosarcoma and congenital mesoblastic nephroma along with the recent availability of targeted therapies directed toward inhibition of NTRK signaling argue for alternate testing strategies beyond ETV6 break-apart FISH. The use of either NTRK3 FISH or next-generation sequencing will expand the number of cases in which an oncogenic fusion is identified and facilitate optimal diagnosis and treatment for patients.
Keywords: dospělí; Genetic Testing; sekvenční analýza RNA; Discoidin Domain Receptor 2; nádory prsu; serinové endopeptidasy; Female; Infant; Repressor Proteins; předškolní dítě; Serine Endopeptidases; novorozenec; represorové proteiny; Adult; ženské pohlaví; Neoplasm Recurrence, Local; Nephroma, Mesoblastic; fúzní onkogenní proteiny; Adolescent; lidé; Infant, Newborn; Breast Neoplasms; Oncogene Proteins, Fusion; Aged, 80 and over; Carcinoma; karcinom; Proto-Oncogene Proteins c-ets; Kidney Neoplasms; protoonkogenní proteiny c-ets; proteiny asociované s mikrotubuly; Cell Cycle Proteins; Fibrosarcoma; Male; kojenec; fibrosarkom; protein ETS, translokační varianta 6; Aged; Child, Preschool; Sequence Analysis, RNA; lokální recidiva nádoru; genetické testování; receptor DDR2; mezoblastický nefrom; nádory ledvin; hybridizace in situ fluorescenční; lidé středního věku; senioři nad 80 let; Microtubule-Associated Proteins; senioři; mužské pohlaví; In Situ Hybridization, Fluorescence; proteiny buněčného cyklu; ETS Translocation Variant 6 Protein; Middle Aged; mladiství; Humans